Penilaian Amali Sains Sekolah Rendah: Satu Kajian Perintis - Ivan Filmer, Ivan Filmer; Poh , Swee Hiang (Penerbit Universiti Sains Malaysia, 1997)
In line with the aim of producing a science oriented and progressive society, Science was reintroduced as a subject in the primary school curriculum in December, 1994. It is also an examination subject in the UPSR since 1997. Other than testing for content knowledge, aspects such as scientific skills, attitudes and moral values should also be assessed